BUS RAPID TRANSIT POLICY IN MUNICIPAL CITY OF BANDAR LAMPUNG - Dedy Hermawan; Simon Sumanjoyo (Spirit Publik: Jurnal Administrasi Publik, 2016)
The aim of the research is to describe and discess the policy cycle of Bus Rapid Transit, the polemic in the policy of bus rapid transit, and the involvement of the stakeholder and their role in bus rapid transpit policy in Bandar Lampung. This research uses post positivistic paradigm with the approach of qualitative descriptive research method. This research resulted as: firstly, the bus rapid transit is an derivative regulation of Act No. 22 2009 regarding Traffic and Road  Transport, aimed to reduce traffic jam in Bandar Lampung city. Secondly, the policy of bus rapid transit was arranged stage-by-stage with a full iniative from the Municipal goverement of Bandar Lampung, collaborated with the leading sector from Transportation Bureau of Bandar Lampung, involving PT Trans Bandar Lampung as the management in charge. Thirdly, there was a polemic of bus rapid transit policy regarding the monopoly of route of people transportation by the bus rapid transit, special treatment to bus rapid transit which don’t pay bus station retribution which is unfair, and there was some illegal fees on the employee in PT Trans .Bandar Lampung. Fourthly, the of bus rapid transit involves many stakeholders, such as Ministry of Transportatio of The Republic of Indonesia, |Transportation Bureau of Bandar Lampung City, The Regional Representatives Council of Bandar Lampung, Road Transportation Organization of Bandar Lampung, PT. Trans Bandar Lampung, Perum DAMRI Bandar Lampung, Lampung Region of Indonesia Transportation Society, Communication Forum of Public Car Transportation Bandar Lampung, CV. Devis Jaya, and also Indonesian Police and Civil Servant Security Forces. Keyword: Public policy, Transportation, Bus Rapid Transit